2016
DOI: 10.1063/1.4945576
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and thermal properties of three-dimensional printed multilayered nano-carbon/poly(lactic) acid structures

Abstract: A new type of lightweight material produced by 3D printing consisting of nano-carbon doped polymer layer followed by a dielectric polymer layer is proposed. We performed temperature dependent characterization and measured the electromagnetic (EM) response of the samples in the GHz and THz range. The temperature dependent structural characteristics, crystallization, and melting were observed to be strongly affected by the presence and the number of nano-carbon doped layers in the sandwich structure. The electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 29 publications
(31 reference statements)
1
39
0
Order By: Relevance
“…The high aspect ratio, as well as the high elec trical conductivity of GNP particles, generally define their EM properties in the microwave and THz ranges and make these carbon additives very promising for solving problems related to effective broadband absorption and shielding of EM radiation. In particular, PLA filled with GNP, carbon nano tubes, and other nanocarbons is one of the best candidates to produce layered structures or structures with different sophisticated geometries via additive manufacturing (see for example [25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…The high aspect ratio, as well as the high elec trical conductivity of GNP particles, generally define their EM properties in the microwave and THz ranges and make these carbon additives very promising for solving problems related to effective broadband absorption and shielding of EM radiation. In particular, PLA filled with GNP, carbon nano tubes, and other nanocarbons is one of the best candidates to produce layered structures or structures with different sophisticated geometries via additive manufacturing (see for example [25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…PLA/mHA showed no significant T g,PLA change. As the TG results showed that only 1.4 wt% KH560 was grafted on the HA surface, which could not confine the mobility of the PLA chains, the HA nano fillers had a negligible effect on T g,PLA . An exothermic peak at ∼108°C is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Summarizing, we can conclude that along with polymer composites comprising graphene (see Ref. ), such thin films can be very suitable materials for producing effective absorbers, electromagnetic shielders, for design of high‐frequency power detectors and sensors for microwave and THz radiations.…”
Section: Discussionmentioning
confidence: 92%
“…The effective thin films conductivity (see Table ) was extracted from the experimental data using the procedure detailed elsewhere . In the numerical calculation, the dielectric permittivity of pure quartz was set as 3.8 + 0.025i.…”
Section: Resultsmentioning
confidence: 99%